2010
DOI: 10.1093/pasj/62.5.l43
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Jet Model: Magnetically Collimated, Radiation-Pressure Driven Jet

Abstract: Relativistic jets from compact objects are ubiquitous phenomena in the Unvierse, but their driving mechanism has been an enigmatic issue over many decades. Two basic models have been extensively discussed: magnetohydrodynamic (MHD) jets and radiation-hydrodynamic (RHD) jets. Currently, the former is more widely accepted, since magnetic field is expected to provide both the acceleration and collimation mechanisms, whereas radiation field cannot collimate outflow. Here, we propose a new type of jets, radiation-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 39 publications
4
36
2
Order By: Relevance
“…In addition, the magnetic fields affect the geometrical structure of jets. Takeuchi et al (2010) performed axisymmetric two-dimensional radiation MHD simulations and found that the jet is collimated by magnetic stress, while it is accelerated by radiative force. Therefore, the structure of the jet and the outflow is affected by magnetohydrodynamical processes.…”
Section: Comparison With Observations Of Ulxsmentioning
confidence: 99%
“…In addition, the magnetic fields affect the geometrical structure of jets. Takeuchi et al (2010) performed axisymmetric two-dimensional radiation MHD simulations and found that the jet is collimated by magnetic stress, while it is accelerated by radiative force. Therefore, the structure of the jet and the outflow is affected by magnetohydrodynamical processes.…”
Section: Comparison With Observations Of Ulxsmentioning
confidence: 99%
“…Therefore, an accretion disk threaded by ordered magnetic field lines is therefore always sub-Keplerian (Ogilvie & Livio 1998, 2001Cao & Spruit 2002;Cao 2012). Radiationmagnetohydrodynamic simulations have been carried out on the global structure of the accretion disks and outflows around black holes (e.g., Moscibrodzka et al 2007;Mościbrodzka & Proga 2009;Takeuchi et al 2010;Ohsuga & Mineshige 2011;Vaidya et al 2011). It has been found that the magnetic force, together with the radiation force exerted by accretion disks, can efficiently drive outflows from luminous accretion disks.…”
Section: Introductionmentioning
confidence: 99%
“…To see what force is responsible for the acceleration and collimation of the jet, we evaluate the time-averaged strengths of the vertical components of the gravitational force, the gas-pressure force, the radiation-pressure force, and the Lorentz force [13]. The result is that the jet is accelerated by the radiation-pressure force, while the Lorentz force contributes much to the collimation.…”
Section: Radiation-mhd Jetmentioning
confidence: 99%